Regulasi Terhadap Pemasangan Alat Peraga Kampanye Di Area Terlarang Dan Penegakan Hukumnya - Sinambela, Michael Bima Martua; Siregar, Hisar (Innovative: Journal Of Social Science Research, 2025)
This research uses normative legal research methods to analyze the installation of campaign props in prohibited areas and law enforcement. Installing campaign props (APK) is a form of strategy used by candidates and political parties in conveying their vision, mission and work programs to the public during the campaign period. APKs include banners, billboards, posters and various other media placed in public spaces. However, installing APKs often causes various problems, especially when carried out in prohibited areas, such as places of worship, public facilities and government facilities. Regulations governing the installation of APKs are contained in various laws and regulations, such as the Election Law and KPU Regulations. Violations of this rule can disrupt the aesthetics of the city, damage public order, and have the potential to cause conflict between supporters. Law enforcement against violations of installing APKs in prohibited areas is a challenge for election supervisors and related agencies. There are several factors that influence the effectiveness of law enforcement, including the lack of awareness of election participants regarding regulations, limited supervisory resources, and weak coordination between institutions. Law enforcement efforts include preventive measures through socialization of regulations and repressive measures in the form of issuing or removing APKs that violate the rules.